Hairy Indigo Control in Peanut - Jason Ferrell; Blaire Colvin; Pratap Devkota (EDIS)
This publication provides county Extension agents, growers, and pesticide applicators with information on hairy indigo control options in peanut. Written by Jason Ferrell, Blaire Colvin, and Pratap Devkota, and published by the UF/IFAS Agronomy Department, revised May 2021.